Consider the graph of the quadratic graph y=-x^2 -10x+24 ,what is the y-value of the vertex

Answers

Answer 1

-51

First, find the axis of symmetry, or the x value where the line switches directions. This is also the x value of the vertex. Find this by using the equation -b/2a. In this case, -10 is b, and 1 is a.

-(-10)/2(1)

10/2

5

So, the x value of the vertex is 5. Now, find the y value by putting the x value back into the equation.

y = -(5)^2 - 10(5) + 24

y = -25 - 50 + 24

y = -75 + 24

y = -51

So, the y value of the vertex is -51.


Related Questions

If a high school sophomore randomly declares himself a leader to his classmates, he will have difficulty finding people who will listen to him. Why?

People are less likely to obey people that are just like themselves.
People are more likely to obey someone who represents authority.
People are less likely to obey others who are currently in school.
choices a and b

Answers

Answer:

I think the awnser should be a.

Step-by-step explanation:

This is because people usally find interests in things that percieve them. Since I am in freshmen I can tell how you feel. If you want to be a leader make choices that affect people personally, and don't make them feel bad.

Answer:

A is the answer.

Step-by-step explanation:

If a high school sophomore randomly declares himself a leader to his classmates, he will have difficulty finding people who will listen to him.

This is because - People are less likely to obey people that are just like themselves.

People are more likely to obey someone who represents authority. This cannot be the answer as the kid has not been declared authority by the school or he is not elected by the students. A random kid self electing himself will not be taken seriously by the kids.

So, option A can be the answer.

i am a number. my number squared is equal to 1/16. hat number am i

Answers

Answer: 1/4

Step-by-step explanation: 1/4 x 1/4= 1/16

1.
Identify the hypothesis and conclusion of this conditional statement:

If two lines intersect at right angles, then the two lines are perpendicular.

Hypothesis: The two lines are not perpendicular.
Conclusion: Two lines intersect at right angles.

Hypothesis: Two lines intersect at right angles.
Conclusion: The two lines are not perpendicular.

Hypothesis: The two lines are perpendicular.
Conclusion: Two lines intersect at right angles.

Hypothesis: Two lines intersect at right angles.
Conclusion: The two lines are perpendicular.

Answers

it is the second one

Answer: Hypothesis: Two lines intersect at right angles.

Conclusion: The two lines are not perpendicular.

Step-by-step explanation:

A conditional statement is written as "if p then q" , where symbol 'p' represents the hypothesis and symbol 'q' represents the conclusion.

For example : If a coin has two heads , then the coin is biased.

here , Hypothesis : a coin has two heads

Conclusion : coin is biased

Given conditional statement : If two lines intersect at right angles, then the two lines are perpendicular.

Here, Hypothesis: Two lines intersect at right angles.

Conclusion: The two lines are not perpendicular.

PLEASE HELP!!
Find the exact circumference of the circle.

Answers

Answer:

B

Step-by-step explanation:

does anyone know any of these bc my brother needs help and i don’t know!?!?!?

Answers

Answer:

the third one all the way to the right

Step-by-step explanation:

the other two have two or more congruent sides and that one doesnt and also the one that doesn'r belong has a right angle and the others dont

Find the radius of the circle whose equation is x^2 + y^2 = 4.

Answers

Answer:

Radius of the given circle is r = 2.

Step-by-step explanation:

Given equation of the circle is [tex]x^2 + y^2 = 4[/tex].

Now we need to find the radius of the given circle [tex]x^2 + y^2 = 4[/tex].

To find that let's compare with the formula of the circle with is [tex]x^2 + y^2 = r^2[/tex], where r is the radius.

We get [tex]r^2 = 4[/tex]

take square root of both sides.

[tex]r=2[/tex]

Hence radius of the given circle is r = 2.

ANSWER

The radius is 2

EXPLANATION

The given equation of the circle is

[tex] {x}^{2} + {y}^{2} = 4[/tex]

.This is the same as

[tex]{x}^{2} + {y}^{2} = {2}^{2} [/tex]

We campare to the equation of the circle with center at the origin.

[tex]{x}^{2} + {y}^{2} = {r}^{2} [/tex]

We have

[tex]r = 2[/tex]

.Hence the radius of the circle is 2

what is the question mark represent
15/100=375/?

Answers

hey so here ya go, ? = 2500 :)

Answer:

56.25

Step-by-step explanation:

A simple way to answer questions like these is to

Step 1: Multiply 15 and 375. This equals = 5625

Step 2: divide 100 and 5625. This equals = 56.25

2.
If a mouse eats grass seeds, the mouse is a _____.

producer

herbivore

decomposer

carnivore

Answers

Answer:

Herbivore

Step-by-step explanation:

The mouse isnt a producer because he cannot make his own food

The mouse isnt a carnivore because he isnt eating meat

The mouse isnt a decomposer because he isnt breaking down dead or decaying organisms

Herbivores are animals that eat vegetables or greens/plants but not meat.

Answer:

herbivore

Step-by-step explanation:

solve using the elimination method -4x+2y=8 4x+4y=28​

Answers

Answer:

x = -1

y = 6

Step-by-step explanation:

Equation (1) : -4x + 2y = 8

Equation (2) : 4x + 4y = 28​

(1) + (2):

6y = 36

y = 6

Sub y = 6 into (1):

-4x + 2(6) = 8

-4x + 12 = 8

-4x = -4

x = -1

What is the answer to number 4.

Answers

Answer: 2x-7, 2+4.

Explanation: An expression is a mathematical phrase that has a + or - but no equal sign.

find the area of the figure

50cm^2
127cm^2
144.5cm^2
172cm^2

Answers

Answer:

this gives you 144.5cm^2 and that is your answer

I hope my answer has come to your helpanswerStep-by-step explanation:

The area of the given figure is Option(C) 144.5 square centimeter.

What is the area of the given figure in the diagram ?

In the diagram given aside, two shapes are mentioned one is a rectangle and other is a right-angled triangle.

The area of the rectangle is given by -  length*breadth

The area of the right-angled triangle is given by -  1/2*base*height

In the given figure, length = 13cm , breadth = 9cm , base = 11cm and height = 5cm

⇒ Total area = length*breadth + 1/2*base*height

⇒ Total area = 13*9 + 1/2*11*5 square centimeter

⇒ Total area = 117 + 27.5 square centimeter

∴  Total area = 144.5 square centimeter

Therefore, the area of the given figure is Option(C) 144.5 square centimeter.

To learn more about area of figure, refer -

https://brainly.com/question/1090412

#SPJ2

Julien interviewed his classmates on which course they prefer and which animal they prefer. What percentage of cat lovers also prefer French?

Answers

Answer:

66.6%

Step-by-step explanation:

simplify by rationalizing the denominator: 4 over the square root of 10 minus square room of 6 ​

Answers

Answer:

[tex]\large\boxed{\dfrac{4}{\sqrt{10}-\sqrt6}=\sqrt{10}+\sqrt6}[/tex]

Step-by-step explanation:

[tex]\dfrac{4}{\sqrt{10}-\sqrt6}\\\\\text{use}\ (a-b)(a+b)=a^2-b^2\ \text{and}\ (\sqrt{a})^2=a\\\\=\dfrac{4}{\sqrt{10}-\sqrt6}\cdot\dfrac{\sqrt{10}+\sqrt6}{\sqrt{10}+\sqrt6}=\dfrac{4(\sqrt{10}+\sqrt6)}{(\sqrt{10})^2-(\sqrt6)^2}=\dfrac{4(\sqrt{10}+\sqrt6)}{10-6}\\\\=\dfrac{4(\sqrt{10}+\sqrt6)}{4}=\sqrt{10}+\sqrt6[/tex]

The rationalization of the given expression will be equal to

[tex]\dfrac{4}{\sqrt{10}-\sqrt{6}}=\sqrt{10}+\sqrt{6}[/tex]

What is rationalization?

Rationalization is a procedure used in elementary mathematics to remove the irrational number from the denominator.

The rationalization of the given fraction will be :-

[tex]=\dfrac{4}{\sqrt{10}-\sqrt{6}}\times \dfrac{\sqrt{10}+\sqrt{6}}{\sqrt{10}+\sqrt{6}}[/tex]

[tex]\dfrac{4\sqrt{10}+\sqrt{6}}{\sqrt{10}^2-\sqrt{6}^2}=\dfrac{4\sqrt{10}+\sqrt{6}}{10-6}[/tex]

[tex]\dfrac{4\sqrt{10}+\sqrt{6}}{\sqrt{10}^2-\sqrt{6}^2} =\dfrac{4\sqrt{10}+\sqrt{6}}{4}=\sqrt{10}+\sqrt{6}[/tex]

Hence rationalization of the given expression will be equal to

[tex]\dfrac{4}{\sqrt{10}-\sqrt{6}}=\sqrt{10}+\sqrt{6}[/tex]

To know more about rationalization follow

https://brainly.com/question/14261303

#SPJ2

What is the simplified form of this expression?

Answers

Answer:

[tex]\large\boxed{7c^2d-7c+4d-10}[/tex]

Step-by-step explanation:

[tex]5c^2d-4c+3d-3+2c^2d-3c+d-7\qquad\text{combine like terms}\\\\=(5c^2d+2c^2d)+(-4c-3c)+(3d+d)+(-3-7)\\\\=7c^2d-7c+4d-10[/tex]

The area of the base of a rectangular prism is 36 cm2. The height of the prism is 3
5
6
cm. What is the volume of the prism?

Answers

Answer:

Height 356: 12816 cm3

Height 6: 216 cm3

Height 5: 180 cm3

Height 3: 108 cm3

Step-by-step explanation:

base * height = volume

A set of stairs is being built as shown. The length of each stair is 11 inches. What is the rise, r, for each stair? Round to the nearest inch.

2 inches
7 inches
17 inches
24 inches

Answers

Answer:

7 inches just took test

Step-by-step explanation:

The rise, r, for each stair is 7 inches.

What is Trigonometry?

Trigonometry is a branch of mathematics that studies relationships between side lengths and angles of triangles.

From the given figure the  length of each stair is 11 inches.

We have to find the rise of each stair.

From the pythagoras theorem we find the value of r.

In a right-angled triangle, the square of the hypotenuse side is equal to the sum of squares of the other two sides“.

11²+r²=13²

121+r²=169

r²=169-121

r²=48

Take square root on both sides

r=6.9

r= 7 inches.

Hence, the rise, r, for each stair is 7 inches.

To learn more on trigonometry click:

https://brainly.com/question/25122835

#SPJ2

Slove -4(x+1)-3=(x-4)

Answers

Answer:

[tex]x=-\frac{3}{5}[/tex]

Step-by-step explanation:

[tex]-4(x+1)-3=(x-4) \\ \\ -4x-4-3=x-4 \\ \\ -4x-7=x-4 \\ \\ -7=5x-4 \\ \\ 5x=-3 \\ \\ x=-\frac{3}{5}[/tex]

- 4 ( x + 1) - 3 = ( x - 4)

Distribute- 4x - 4 - 3 = (x - 4)

    2. Take away the parenthesis at the end

- 4x - 4 - 3 = x - 4

    3. Combine like terms

- 4x - 7 = x - 4

    4.  Add 4x to each side

-7 = -3x - 4

    5. Add 4 to each side

-3 = -3x

    6.  Divide

-3 / -3 = -3x / -3x = 1

Yuma is solving the inequality 3x−23≥−5.

To solve the inequality, he begins by solving the equation as shown.

Which number line represents the solution to the inequality?

Urgent answer plz. Thank u.

Answers

[tex]3x \geqslant 23 - 5 \\ 3x \geqslant 18 \\ x \geqslant 6 \\[/tex]

Answer:      x≥ 6

Step-by-step explanation:

To solve this inequality

3x - 23 ≥ -5

First, what you need to do is to add 23 to both-side of the inequality, Hence;

3x  -23  +  23  ≥ -5 + 23

(-23 + 23  = 0,   also  -5 +  23  = 18)

3x   ≥   18

To get the value of x, we need to divide both-side of the inequality by 3

3x /  3       ≥   18/3

(On the left hand side of the equation, the three at the numerator will cancel out that of the denominator, then on the right hand side of the equation, 3 will divide 18 which will give 6)

x ≥    6

Select the expression that is equivalent to (x-3)^2

Answers

The answer is C. X^2-6x+9

Answer:

C. [tex]x^2-6x+9[/tex]

Step-by-step explanation:

We have the expression [tex](x-3)^2[/tex] we can rewrite it as:

[tex](x-3)^2=(x-3)(x-3)[/tex] and solve it with distributive property or we can use the formula to multiply a binomial by itself. The formula is:

[tex](a+b)^2=a^2+2ab+b^2[/tex]

or

[tex](a-b)^2=a^2-2ab+b^2[/tex]

Then:

[tex](x-3)^2=x^2-2.x.3+3^2\\(x-3)^2=x^2-6x+9[/tex]

The correct option is C. [tex]x^2-6x+9[/tex]

Assume that two chords in a given circle are congruent. Which of the following must also be true?

Answers

Answer:

If the two chords are congruent, then they must be equidistant from the centre of the circle. 

Ans: D

The diagram attached below shows that if two congruent chords are in a given circle, a statement that will be true is:

the two congruent chords must be equidistant from the center of the circle.

Facts about congruent chords in a given circle:

The diagram attached below shows two chords that have the same length in the given circle O.

The diagram shows that distance from the midpoint of one chord to the center of the circle, O, is the same as the distance from the middle of the other chord to center, O.

The diagram attached below therefore shows that if two congruent chords are in a given circle, a statement that will be true is:

the two congruent chords must be equidistant from the center of the circle.

Learn more here:

https://brainly.com/question/2364467

What is the input value for the following function if the output value is 5? y = x - 3

Answers

The input value is the x value, and the output value is the y value.

You know y = 5, so you can plug it into the function to find the input:

y = x - 3         Plug in 5 for y

5 = x - 3      Add 3 on both sides

5 + 3 = x - 3 + 3

8 = x

Answer:

8

Step-by-step explanation:

y= x -3

to get the Anwer I got i Subtracted

Because the output value is supposed to be five so?

5= x-3

Well  2 does get 5 if you add 2+ 3 together!

but if you subtract 3 -2 you get 1..

and 5 - 3 = 2 not 5

and adding 8 + 3 is 11 but subtracting it is 5!

which is

5= 8 - 3

Find the first three iterates of the function f(z) = 2z + (3 - 2i) with an initial value of z0 = 4.

Answers

Answer:

First Iterate: 11-2i

Second Iterate: 25-6i

Third Iterate: 53-14i

Step-by-step explanation:

Given:

f(z)=2z+(3-2i)

And  

z_0=4

For the first iterate we have to put the value of z0 into the function in place of z.

First Iterate:

z_1=f(z_0 )=2z_0+(3-2i)

=2(4)+(3-2i)

=8+3-2i

=11-2i

Second Iterate:

For the second iterate we have to put the value of z1 into the function in place of z.

z_2=f(z_1 )=2z_1+(3-2i)

=2(11-2i)+(3-2i)

=22-4i+3-2i

=25-6i

Third Iterate:

For the third iterate we have to put the value of z2 into the function in place of z.

z_3=f(z_2 )=2z_2+(3-2i)

=2(25-6i)+(3-2i)

=50-12i+3-2i

=53-14i

Answer:d

Step-by-step explanation:

Cuz

Select one of the factors of the quadratic expression.

x2 + 5x - 14

Answers

Answer:

(x + 7) or (x - 2)

Step-by-step explanation:

Given

x² + 5x - 14

Consider the factors of the constant term (- 14) which sum to give the coefficient of the x- term (+ 5)

The factors are + 7 and - 2, since

7 × - 2 = - 14 and 7 - 2 = + 5, hence

x² + 5x - 14 = (x + 7)(x - 2)

Which of the following integers represents the opposite of the opposite of 4?

4
-4
1/4
-1/4

Answers

Answer:

[tex]4[/tex]

Step-by-step explanation:

To find the opposite of the opposite, multiply the given number by -1 twice, or just 1 since [tex]-1*-1=1[/tex].

[tex]4*-1*-1=4[/tex] or [tex]4*1=4[/tex]

Final answer:

The opposite of a number is its additive inverse. Therefore, the opposite of the opposite of a given number will always be the original number itself. In this instance, the opposite of the opposite of 4 is 4.

Explanation:

The question asks for the opposite of the opposite of a given number. In mathematics, the 'opposite' of a number is its additive inverse. If the original number is positive, its opposite is the same number as a negative. Vice versa, if the original number is negative, its opposite would be positive. For example, the opposite of 4 is -4 and the opposite of -4 is 4.

So let's apply this concept to the given number, which is 4. The opposite of 4 is -4. Now, the opposite of -4 is 4. Hence, the opposite of the opposite of 4 is 4.

Learn more about Opposites in Mathematics here:

https://brainly.com/question/36830748

#SPJ2

a restaurant owner has a large trash container in the shape of a rectangular prism with a height of 4 ft and a base that is 4 ft wide by 6 feet long. during a one month period the container needed to be empty 4 times. how many cubic feet of trash were taken away during the month?

96 ft^3

192 ft^3

288 ft^3

384 ft^3​

Answers

Answer:384ft^3

Step-by-step explanation:

4x4=16x6=96x4=384^3

Answer:

D) 384

Step-by-step explanation:

i just took the test

It’s possible to build with side lengths 3,3,9

Answers

NO!

3+3 > 9

This does not form a triangle.

what are the minimum, first quartile, 20 70 13 15 23 17 40 51

Answers

Answer:

Minimum 13

First quartile 16

Step-by-step explanation:

Rewrite the sample 20 70 13 15 23 17 40 51 in ascending order:

13  15  17  20  23  40  51  70

The minimum is 13.

The median is the middle number

13  15  17  20  23  40  51  70

The middle number between 20 and 23 is

[tex]\dfrac{20+23}{2}=21.5[/tex]

Consider first half of the sample

13  15  17  20

The first quartile is the middle number of this part. The middle number of

13  15  17  20

is

[tex]\dfrac{15+17}{2}=16[/tex]

HELPPPPPPPPPP Add & subtract matrices .....

PLZ GIVE THE ANSWER .. THANKSSSSS .

Answers

Answer:

[tex]\left[\begin{array}{cc}0&-1\\-1&0\\-1&-1\end{array}\right][/tex]

Step-by-step explanation:

In this question we have to subtract the corresponding entries of column of matrix 1 and the matrix 2 corresponding entries

[tex]=\left[\begin{array}{cc}-1&0\\1&-2\\1&3\end{array}\right]-\left[\begin{array}{cc}-1&1\\2&-2\\2&4\end{array}\right] \\=\left[\begin{array}{cc}-1-(-1)&0-1\\1-2&-2-(-2)\\1-2&3-4\end{array}\right]\\=\left[\begin{array}{cc}-1+1&-1\\-1&-2+2\\-1&-1\end{array}\right]\\=\left[\begin{array}{cc}0&-1\\-1&0\\-1&-1\end{array}\right][/tex]

what does one centimeter equal

Answers

[tex]1\text{cm}=1\cdot10^{-2}\text{m}=10^{-2}\text{m}[/tex]

Answer:

Step-by-step explanation:

1 cm = 10 mm = 0.01 m = 0.00001 km

Number 14 please! An Astronaut standing on the moon would weigh about 16% of her weight on earth. If an astronaut Weighs 150 pounds on earth, about how much would she weigh on the moon?

Answers

Answer: 24 pounds

weight on moon=(.16)(weight on earth)

weight on moon= (.16)(150)=24

Other Questions
What are the solutions of the quadratic equation (x 8)2 13(x 8) + 30 = 0? Use u substitution to solve. x = 11 and x = 18 x = 2 and x = 5 x = 2 and x = 5 x = 11 and x = 18 What is angle E and what is the process finding it? Type the correct answer in the box. If cos x = sin(20 + x) and 0 < x < 90, the value of x is . By 1935 the proportion of women workers in the ussrs workforce was _________in every five. Find the area and perimeter of the triangle below if a = 164 feet, b=221 feet, c=352 feet, and h=76 feet The probability for success of an event is P(A), and the probability of success of a second event is P(B). What is theprobability of both events occurring, in that order?A.) P(A + B) B.) P(A) . P(B) C.) P(A) + P(B) D.) P(A x B) A 4-digit number ends in 3. If you put the number 3 in the first position, the number will decrease by 738. Find the original 4-digit number? what is 25 1/2 5 3 = 5 x Please help me with this and thank you What music tour that started in 1995 was sponsored by vans shoes? The equation for a circle is x28x+y22y8=0 .What is the equation of the circle in standard form?(x16)2+(y1)2=25(x16)2+(y1)2=16(x4)2+(y1)2=25(x4)2+(y1)2=16 The monotheistic religion of the Israelites included a belief system based on personal responsibility and equal rule. Which statement reflects this belief system? Half of a number, x, increase by 7 is greater than -11 and less than-3. What are the possible solutions? Fill in the blank _____ Is Genetic information in the cells of all living things A particular fruit's weights are normally distributed, with a mean of 786 grams and a standard deviation of 15 grams.If you pick 10 fruits at random, then 20% of the time, their mean weight will be greater than how many grams?Give your answer to the nearest gram. The Party is the oldest political party in the United States. dentify the adverbs: An unprecedented use of central bank actions is now showing itself to be increasingly ineffective. A.now, increasinglyB.unprecedented, ineffectiveC.central, now, itself D.increasingly, ineffective What tone does Antony use when speaking to Octavius Quadratic relations help needed! Thank you In terms of a painting, composition refers to_____. 1. color choice 2. imagery 3. organization of the painting's various images on the canvas 4. style